Whose Agency? Looking Forward to the Virtual Research Council - Caswill, C (Routledge, 2005)
This paper has three parallel ambitions: to consider the potential impact of large-scale use of modern information and communication technologies (ICTs) through the device of an imagined ‘virtual’ research council (VRC); to discuss this imagined future from the principal-agent perspective of research councils as intermediary agencies; and to draw conclusions for the future of research funding institutions, and the influences operating upon them. It proposes some generic characteristics of today's research councils, and blends those with leading-edge ICTs to create the prospect of an intermediary research funding agency, making full use of electronic communication. This VRC emerges with important differences from today's national research councils, while retaining underlying core characteristics. It will be more effectively connected to applicants, clients, advisers, stakeholders and ministries. The time taken for decisions and their communication will be hugely reduced. It will have the capacity to base strategic and individual funding decisions on more and better information. There will be new opportunities to monitor and evaluate progress, outcomes and impact. Operating costs can be reduced, primarily through savings on travel and subsistence for its committee advisers. It will be restructured to adjust to the changing internal skill base and to take advantage of opportunities for new interactions with its environment. The persistent characteristics include dependence on the environment for the flow of new ideas, a mix of responsive and priority funding, and the use of some version of peer review as the main basis for funding decisions. The paper then uses a principal-agent perspective to analyse four dimensions of this imagined future - delegation, connectivity, decision uncertainty, and the dynamics of innovation and influence. It ends with some conclusions about the future development of research councils, about their use of modern ICTs, and about the other influences that will shape their future.